الأبعاد التّربويّة للتّواصل اللّغويّ الكتابيّ في منهاج الجيل الثّاني للتّعليم المتوسّط الخاصّ باللّغة العربيّة - دحماني, عبد الحفيظ; ولهاصي, نجيدة (جامعة الوادي - University of Eloued, 2021)
ملخّص: لا يخفى على أيّ باحث أنّ الوظيفة الأساس للّغة هي التّواصل، لكنّ التّواصل ليس هدفا في حدّ ذاته بقدر ما هو منصّة لتلبية مجموعة من الأغراض. ومن الأغراض الّتي سنتعرّض لها في هذه الدّراسة الغرض التّربويّ للتّواصل الكتابيّ، وذلك بالوقوف على الأبعاد التّربويّة للتّواصل اللّغويّ الكتابيّ، أمّا الجانب التّطبيقيّ للدّراسة فقمنا باستطلاع تجلّيات ذلك في منهاج الجيل الثّاني للّغة العربيّة الخاصّ بالتّعليم المتوسّط وصفا وتحليلا. وأبرز النّتائج المتوصّل إليها أنّ التّواصل اللّغويّ الكتابيّ وسيلة لتمرير قيم تربويّة للمتعلّم. ومن ضمن التّوصيات الّتي كلّلنا بها الدّراسة ضرورة اختيار مؤلّفي الكتب المدرسيّة لنصوصٍ تستجيب للقيم التّربويّة الّتي تتناسب مع مجتمعنا الجزائريّ. Abstract: It is no secret to any researcher that the primaryfunction of language is communication, but communication - verbally or in writing - is not as much a goal in itself as a bridge to meet a range of purposes. The educational purpose of this study is written communication by examining the educational dimensions of written linguistic communication. As for the practical aspect of the study, we conducted a survey of the manifestations of this in the second generation curriculum of the Arabic language for medium-term education(middle school), description and analysis. The most notable findings are that written language communication is a way of passing educational values to the learner through reading texts. One of the recommendations we have been asked to make is the need to select the authors of school textbooks for texts that correspond to the educational values that suit our Algerian society. Keywords: Educational dimensions, Written linguistic communication, second generation Arabic curriculum, intermediate education(middle school).
مقال
Keywords: الأبعاد التّربويّة؛ التّواصل اللّغويّ الكتابيّ؛ منهاج الجيل الثّاني للّغة العربيّة؛ التّعليم المتوسّط